PENGARUH SISTEM INFORMASI AKUNTANSI DAN PEMAHAMAN AKUNTANSI TERHADAP KUALITAS LAPORAN PENGGAJIAN PADA PT. BUDIMAN INDAH PERKASA - Hamta, Firdaus (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
This study aimed to determine the effect of accounting information systems and accounting understanding of the quality of payroll report on PT. Budiman Indah Perkasa.This study analyzes the quality of the payroll report on PT. Budiman Indah Perkasa with a population of 86 people by distributing questionnaires to 46 respondents. This study data processing using SPSS ver. 16. As for testing the data used to test the R - Square, regression and coefficient of determination.The results showed that the information accounting system and accounting understanding no significant effect on the quality of the payroll report on PT. Budiman Indah Perkasa with smaller f value of sig thus accounting information systems and understanding of accounting does not significantly affect the quality of the payroll report in PT. Budiman Indah Perkasa.Â Keywords: accounting information systems, understanding of accounting and payroll reporting quality.